Implementasi Model Penta Helix dalam Perencanaan Program CSR Peningkatan Hasil Tangkap Ikan Berbasis Teknologi - Isa Elfianto; Fajar Miftakhul Rizqy; Diaz Anthera (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
Program planning is an important first step to develop community empowerment program. The penta helix becomes one of strategies to develop sustainable program of community empowerment. The penta helix model builds a collaborative network of multi-actor roles, including: Academics, Business Sector, Community, Government, and Media. The collaboration can be seen in the planning process of Technology-Based-Fish-Catching Improvement Program initiated by Corporate Social Responsibility PT Pertamina Refinery Unit II Dumai. This study aims to see how the process of the following program, including the role of each stakeholder. The method of this research used descriptive qualitative. The results of this study showed that each stakeholder has their own role in the planning process. There were 7 steps that have been passed during the process, such as; 1) Consideration of program recommendations from academics and proposals submitted by the community (groups); 2) Discussion of CSR Internal Team phase 1; 3) Assessment of the target group; 4) Discussion of CSR Team phase 2; 5) Draft of the initial program scheme by the CSR Team; 6) Involvement of external stakeholder in strengthening program planning; and 7) Formulation of program.